Heterogeneity of Transparent Exopolymer Particles in a Coastal Marine Environment (Sagami Bay, Japan): Seasonal Variation and Its Possible Bacterial Causes - Sugimoto, Kugako; Fukuda, Hideki; Koike, Isao; Nagata, Toshi (Frontiers in Marine Science, 2021)
Transparent exopolymer particles (TEPs) play important roles in the regulation of carbon and pollutant (microplastics and spilled oils) transport in marine environments; however, the factors controlling TEP dynamics in coastal systems have yet to be fully clarified. A widely used colorimetric method quantifies TEPs as a homogeneous pool, which hampers the examination of internal TEP dynamics. Here, we used the microscopy to elucidate the seasonal dynamics of TEP subgroups and their controlling factors in Sagami Bay, Japan. TEPs were classified into three types: those not associated with other types of particles (Type I), those colonized by multiple types of particles (bacteria, algal cells, and detritus) (Type II), and those densely colonized by only bacterial clusters (Type III). Type II was generally the most dominant TEP component in terms of area, except in February, when Type I contributed substantially to the total TEP area. Type III was less abundant in terms of area but contributed substantially (up to 34%) to the total number of TEPs. The mean diameters were 14.0 ± 2.8 μm, 17.0 ± 5.8 μm, and 7.5 ± 0.9 μm for Type I, Type II, and Type III TEPs, respectively. Type I and Type III TEPs likely represent a transient phase of TEP development toward the formation of Type II, characterized by a high turnover and relatively low abundance in terms of area. The power-law slopes of the distributions of each TEP size, which reflected geometric features of the TEPs at steady state, changed dynamically over the seasons. The abundance of each type of TEP was significantly positively correlated with bacterial abundance, suggesting that bacteria are intimately involved in the regulation of internal TEP dynamics in Sagami Bay. Our results highlight the importance of investigating the internal dynamics of TEPs to improve current understanding of their roles in the regulation of carbon and pollutant transfer in marine environments.